Página web para fortalecer el conocimiento general de la Física: un ejemplo de proyecto semillero - Pavón Brito, Christian (2016)
The present paper shows an example of a seed project that emerged in a Physics classroom of an university of Ecuador. The participants in the seed project were six students in a course of third semester: two womenand four men between 19 and 22 years old, together with a tutor. It is detailed the process of development of the project in the classroom during three sessions and it is presented in the results the key parts as the overall objective, specific objectives, the impact and the expected results when the project ends. It is hoped that this work will inspire more teachers to bring project based learning to class, and provides ideas, tips and tools to engage their students.